The Role of Internal Audit in Discovering Accounting Errors: Evidence from University of Karbala - Rassol Abd Aljalil Mahdi, (Technium Social Sciences Journal, 2024)
The purpose of the research was to find out the role of the control and internal auditing department in dealing with financial errors and the reasons for and type of such errors. The opinions of a group of staff of the control and internal auditing department of the University of Kerbala were taken. The findings of the researcher through the research sample responses showed that the Internal Audit Section has a significant role to play in detecting and processing financial errors that occur at work at all stages of the accounting cycle.